Effectiveness of Clove Leaves (Syzygium aromaticum L.) Steeping Repellent to Anopheles sp. - Maria Nindatu; Leny Noya (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2018)
Anopheles sp. is vector that carrying plasmodium which causes the emergence of malaria which is one of the diseases with a high presentation in Indonesia, so it needs special treatment such as using synthetic insect repellent or mosquito repellent herbs. Clove (Syzygium aromaticum L.) is one of the mosquito repellent herbs that has been used for generations by the people of Maluku, by burning their leaves and smoked them in the house. This study aims to determine the repellent of steeping clove leaves (Syzygium aromaticum L.) towards Anopheles sp. The experimental design used was a completely randomized design (CRD). The results obtained were analyzed by Analysis of Variance (ANOVA) then continued with Duncan Test with sig. value is α=0.05 using SAS software. The samples were 18 rats, which were divided into 6 groups. Each group was given steeping clove leaves with a concentration of 0,50%, 1% concentration, 2% concentration, 4% concentration, 6% concentration, and control group. The sample was adapted for a week, then treated for 24 hours. The results showed a repellent effect of steeping clove leaves (Syzygium aromaticum L.) on Anopheles sp mosquitoes smeared on Rattus norvegicus rats, where the effective concentrations were 1%, 2%, 4%, and 6%, so it can be concluded that steeping clove leaves (Syzygium aromaticum L.) has the effect of repelling Anopheles sp.